Interactions, Diffusion, and Membrane Fluctuations in Concentrated Unilamellar Lipid Vesicle Solutions - Kelley, Elizabeth G.; Blick, Emily E.; Prabhu, Vivek M.; Butler, Paul D.; Nagao, Michihiro (Frontiers in Physics, 2022)
Lipid vesicles are widely used as models for cell membranes, hosts for membrane protein studies, and containers for hydrophilic molecules. The vesicle solutions in these applications are usually prepared at a specific lipid concentration; however, because vesicles are solvent-filled structures, the corresponding volume fraction of vesicles is at least a factor of 3 times higher than the corresponding lipid volume fraction and critically depends on the vesicle radii. Here we show that these high-volume fractions result in measurable interactions between the vesicles as well as affect the vesicle diffusion. We show that vesicle solutions with lipid mass fractions, $m_L$, as low as $≈$ 0.004, which corresponds to a lipid concentration of $≈$ 5 mmol/L (mM), not only have a measurable repulsive structure factor ($S(q)$) in small angle neutron scattering (SANS) experiments, but that this structure factor also affects the measured diffusion coefficient at small scattering momentum transfer values ($q$) such as those probed with dynamic light scattering (DLS). The measured diffusion coefficients are further affected by indirect solvent mediated interactions described by a hydrodynamic factor ($H(q)$). Accounting for the concentration-dependence of the vesicle diffusion shows that the lipid concentration dependence measured in neutron spin echo (NSE) spectroscopy is due to differences in the vesicle diffusion coefficients and not the membrane fluctuation dynamics. The results have practical implications for static and dynamic scattering experiments as well as provide interesting insights into the interactions between soft lipid vesicles.